Implikasi Perlindungan Pengunjung Wisata Sawah Padi di Desa Taman Sampang Berbasis Legal Education terhadap Peningkatan Pendapatan Asli Desa - Sheptiana Indah Murianti; Sumriyah Sumriyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The tourism potential in the Sampang Regency area is very good, one of which is rice tourism in Ataman village. Padi tourism offers beautiful views with typical village culinary attractions. However, in rice tourism there are still problems such as visitors not respecting the cultural values ​​and beliefs of the local community and managers also do not have tourist regulations. Therefore, this results in a decrease in tourist visitors so that the contribution of PADes automatically decreases. The research method used is empirical juridical research with a field study approach. Data collection in this research uses several methods including interviews, observation and literature search. The research location is Taman Village, Jrengik District, Sampang Regency. The data analysis method used in this research is descriptive-qualitative. The results of research during the MBKM KKNT show that the management of Rice Fields Tourism in Taman Village is still not well organized, considering that the management pattern of facilities and infrastructure is still lacking, especially the management does not have rules for tourist visitors, so tourism is quite quiet so that PADes decreases. Therefore, the MBKM KKNT program created a legal education program regarding the protection of tourist visitors within the framework of preventive protection. The results are quite satisfactory from the results of the socialization showing that understanding of village officials, tourism managers, the community and tourist visitors has increased, especially understanding of the substance of the Tourism Law and the Village Law. Apart from that, the management makes rules for issuing visitors based on statutory regulations and the management is improved gradually, so that tourist visitors will gradually increase and the Village Paddy will automatically increase and this will all make the Taman Village community prosperous.